PENGARUH PROMOSI, HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PRODUK ELEKTRONIK MEREK POLYTRON - Pitri Sahayu Ubat Ati; Islamudin Islamudin; Meilaty Finthariasari ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This study aims to determine: (1) Effect of Promotion on Consumer Purchase Interests of Polytron Electronic Products on the Population of the East Lingkar Village of Bengkulu City, (2) Effect of Prices on Purchase Interest of Polytron Brand Consumer Electronics Products on Population of the East Circle Village of Bengkulu City, (3 ) The Influence of Product Quality on Consumer Purchase Interest of Polytron brand Electronic Products in Population of the East Lingkar Village of Bengkulu City, (4) The Effect of Promotion, Price and Product Quality Partially and Simultaneously Against the Consumer Purchase Interest of Polytron Brand Electronic Products in Population of the East Lingkar Village of Bengkulu City. This research is a type of research with quantitative descriptive method, wherein the research compares the results of data collection and prove it with numbers in a number of populations and samples that are considered worthy of research. This research is categorized as survey research, where the research instrument is in the form of a questionnaire. The sample in this study was 157 respondents in the population of the East Ring District of Bengkulu City. The instrument validity test uses the Corrected Item Total Correlation Statement, the reliability test uses Cronbach's Alpha, while the data analysis is done using multiple linear regression analysis. The results found that (1) Promotion has an influence on consumer buying interest. This can be seen in the t test which states that it has the value of t_hit> t_ (Î± / 2) (7,288> 1.9729) and (sig Î± = 0,000 <0.050 then H0 in this study is rejected and Ha is accepted. (2) Price has an influence on Purchase Interest Consumers This is seen in the t test which states it has a value of t_hit> t_ (Î± / 2) (2,733> 1.9729) and (sigÎ± = 0,000 <0.05), in this case H0 is rejected and Ha is accepted. (3) Product Quality has an influence on Consumer Purchase Interest.This is seen in the t test which states it has a value t_hit> t_ (Î± / 2) (8,755> 1.9729) and (sig Î± = 0.031 <0.050 then in this case H0 is rejected and Ha is accepted. (4 ) Promotion (X1), Price (X2) and Product Quality (X3) have the influence together to have a significant effect on Consumer Purchase Interest (Y). This can be seen in the F test which states (420,511> 3.8930) and (sig Î± = 0,000 <0.05) This means that H0 is rejected and Ha is accepted. Keywords: Promotion, Price, Product Quality, Consumer Purchase Interest.